1974
DOI: 10.1111/j.1432-1033.1974.tb03780.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism of d-Galactose Dehydrogenases from Pseudomonas saccharophila and Pseudomonas fluorescens. Formation and Rearrangement of Aldono-1,5-lactones

Abstract: 1. b-D-Galactopyranose has been shown by specificity studies and by gas-liquid chromatographic investigations to be the substrate of the D-galactose dehydrogenases from Pseudomonas sacchurophilu and from Pseudomonas fluorescens.2. cc-~-Galactopyranose and the two ring-isomeric D-galactofuranoses are oxidized, at high enzyme concentrations, only after their rate-limiting isomerization into the b-D-pyranose. The open-chained aldehyde form of D-galactose has been likewise excluded as substrate.3. D-Galactono-l,5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…3). Similar non-enzymatic 1,4-lactone formation has been observed previously for D-galactose dehydrogenases (20). Because the rearrangement is an equilibrium reaction, a very small amount of D-galactaro-1,5-lactone exists in solution and explains why this form was observed in the ternary complex crystal structure.…”
Section: Discussionsupporting
confidence: 82%
“…3). Similar non-enzymatic 1,4-lactone formation has been observed previously for D-galactose dehydrogenases (20). Because the rearrangement is an equilibrium reaction, a very small amount of D-galactaro-1,5-lactone exists in solution and explains why this form was observed in the ternary complex crystal structure.…”
Section: Discussionsupporting
confidence: 82%
“…␥-6-Phosphogluconolactone is formed subsequently by the rearrangement of the ␦-6-phosphogluconolactone. It had been established already that some ␦ lactones were spontaneously converted into the ␥ forms without participation of the open chain of the corresponding acids (20). Our kinetic study revealed that each 6-P-G-L is convertible into the other one, the conversion of the ␦-6-P-G-L into the ␥-6-P-G-L being characterized by a higher rate constant than the reverse conversion.…”
Section: ϫ1mentioning
confidence: 77%
“…Table 4 lists the experimentally determined ratios and free enthalpies calculated by van't Hoff's equation for the δǞγ isomerization. It should be noted that the experimentally determined isomer distributions presented here cannot be compared directly with any previously published data, [3,11,41] since all of them were obtained in (buffered) aqueous solutions and, thus, include hydrolysis to the free aldonic acids, which is not observed in the dry DMSO medium employed in our study. [a] By integration of signals in 1 H NMR spectra.…”
Section: Isomerization Reactions Thermodynamic Considerationsmentioning
confidence: 93%
“…10 h for 4a/b (i.e., seven halflives each), while 5a/b requires weeks to attain its equilibrium. Overall, the isomerization process in [D 6 ]DMSO is orders of magnitudes slower than the value of k ϭ 1 min Ϫ1 ϭ 1.67 ϫ 10 Ϫ2 s Ϫ1 observed for 6a in aqueous solution buffered at pH ϭ 6.8, [11] which suggests that, in aqueous solution, the isomerization is susceptible to the general acid/base catalysis that is also observed in the hydrolysis of the lactones and precludes the isolation of 6a from aqueous solution. [42] In addition, the relative rates of isomerization for the lactones 4a and 5a observed by us in [D 6 ]DMSO are opposite to those previously noted in the literature.…”
Section: Mechanistic Considerationsmentioning
confidence: 93%